Phylogenetic studies of the red algal parasite Congracilaria babae (Gracilariaceae, rhodophyta) / Ng Poh Kheng - Ng , Poh Kheng (2015)
Since the first description of red algal parasites in the last century, phylogenetic relationships between most of the red algal host-parasite associations have only been inferred based on the degree of morpho-anatomical similarity between the host and parasite. The limited morphological characters available for taxonomic inference had driven the use of molecular analyses to unravel the evolutionary relationships between red algal parasites and their host. Furthermore, the broad host range of certain red algal parasitic taxa and the possible occurrence of host-switching event can only be revealed using molecular data. In view of the lack of a clear classification scheme supported by molecular data that take into consideration Congracilaria babae, a parasitic alga found on Gracilaria salicornia, this study represents an initiative aimed to clarify the classification of the parasite, particularly the Malaysian samples. It also served to provide insights into the phylogenetic relationships between the parasites with their hosts by integrating the comparative DNA sequence analyses with morphological and anatomical observations. The possibility of these red algal parasitic taxa extending the host range from G. salicornia to other members of Gracilariaceae was also explored. Specimens of G. salicornia bearing red algal parasites were collected from various localities in Malaysia, Singapore, Indonesia, Thailand and Japan for examination. A similar parasitic taxon observed on a Hydropuntia species was also collected. The parasites found on both G. salicornia and Hydropuntia sp. have similar morphology and anatomy – they form pigmented pustules devoid of rhizoids, with spermatangia borne in deep conceptacles and projecting cystocarps with tubular filaments connecting to the pericarp scattering over surface of the pustules. Comparative phylogenetic analyses based on the DNA sequences of nuclear markers recovered a monophyletic clade comprising the red algal parasites found on G. salicornia and Hydropuntia sp.. Morpho-anatomical observations in concert with molecular analyses revealed that these parasites are conspecific, regardless of their host species. Staining reactions from the histological study, as well as the molecular phylogenies inferred from the DNA sequences of the genetic markers belonging to three different genomes (plastid rbcL gene, mitochondrial cox1 gene and nuclear LSU rRNA gene and ITS region), indicated that C. babae most likely have directly evolved from G. salicornia, and later extended its host range to a distantly related Hydropuntia species. Congracilaria babae featured DNA sequences characteristic of G. salicornia, of which the parasite found on G. salicornia had rbcL and cox1 gene sequences identical to those of the host it originated from, while retaining its unique nuclear identity. The position of C. babae in the same genetic species group as G. salicornia supports its transfer to Gracilaria. To conclude, molecular tools are useful in elucidating the phylogenetic relationships between red algal parasites, as well as that between the parasites and their hosts. The use of the plastid rbcL gene and mitochondrial cox1 gene complementary to the nuclear markers is advocated to trace the original host of a red algal parasite.